2015
DOI: 10.1002/crat.201400469
|View full text |Cite
|
Sign up to set email alerts
|

3D printed models of small and large molecules, structures and morphologies of crystals, as well as their anisotropic physical properties

Abstract: Three-dimensional (3D) physical models of atomic structures of crystals, their anisotropic properties and morphologies as well as models of small and large molecules were printed with support from 3D Systems Corporation. Structural information in Crystallographic Information Framework (CIF) files from the Crystallography Open Database and the Protein Data Bank was utilized. Computer programs were either newly developed (Cif2VRML) or enhanced by 3D print file export functions (WinXMorph and WinTensor) in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Perhaps one of the easiest entries into 3D printing is through the production of teaching aids. [29][30][31][32][33][34][35][36] Commercially, the cost of these model sets used in a large classroom setting can often be prohibitive, whereas when printed each individual item can be produced for a fraction of the price if access to a desktop printer is provided. Extension of this concept to other types of teaching aids has seen the production of reaction progress surfaces to represent spectroscopic data in a more engaging format, 37 as well as energy profiles to visualise local and global minima in a simplistic manner.…”
Section: Teaching Aidsmentioning
confidence: 99%
“…Perhaps one of the easiest entries into 3D printing is through the production of teaching aids. [29][30][31][32][33][34][35][36] Commercially, the cost of these model sets used in a large classroom setting can often be prohibitive, whereas when printed each individual item can be produced for a fraction of the price if access to a desktop printer is provided. Extension of this concept to other types of teaching aids has seen the production of reaction progress surfaces to represent spectroscopic data in a more engaging format, 37 as well as energy profiles to visualise local and global minima in a simplistic manner.…”
Section: Teaching Aidsmentioning
confidence: 99%
“…College educators around the world are now producing their own three-dimensional printed crystallographic models (Stone-Sundberg et al, 2015). Their papers are often published in journals and the proceedings of conferences that are dedicated to college education.…”
Section: Three-dimensional Printing In Teaching Crystallographymentioning
confidence: 99%
“…The current 3D printing technologies and the impact of 3D printed models on students’ comprehension and retention of structural information are reviewed in ref. 31 . In one study reported in ref.…”
Section: Introductionmentioning
confidence: 99%